Discounting, inequalities and economic convergence - Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2010)
The aim of this paper is to examine the impact of inequalities and economic convergence on the efficient discount rate, in the absence of any risk-sharing scheme. We consider an economy in which the initial consumption level and the distribution of consumption growth are heterogeneous. The benchmark case is when inequalities are permanent and relative risk aversion is constant. The discount rate is not affected by inequalities in that case. We first relax the assumption on risk aversion, and we derive conditions under which permanent inequalities reduce the discount rate. If relative prudence is larger than unity, an increase in economic convergence always raises the efficient discount rate. In a realistic calibration exercise, we show that the effect of economic convergence is to triple the discount rate, from less 2% to more than 6%.
Keywords: G00; 330; prudence; temperance; concordance; discount rate; Soziale Diskontrate; Soziale Ungleichheit; Entwicklungskonvergenz; Risikoaversion; Theorie